Design and emotion: methods and technique for emotional evaluation of fashion goods (ModaPalavra e-periódico, 2020)
The presentation of methods and techniques for the emotionalstudy of products is proposed, with a clipping of research forfashion goods. The kansei engineering method will beexplored in a descriptive and applied way, to help understandthe emotions that users confer on products. Using focus grouptechniques, the objectives are to discuss the fashion andconsequent selection of data to use with the method. Inaddition, theconstruction and application of the semanticdifferential scale will be used to record users’ emotionalimpressions. The results, obtained with the applied methodassociated with the techniques; aim to present therelationship between the interviewees’ emotional perceptionand design elements of the fashion goods that compose aclothing structure. Hence, the emotional significanceattributed by users to products can be understood andconverted into design requirements to develop new products.The presentedmethod associated to the techniques isconsidered efficient and may be integrated to the practice ofdesign
Keywords: emotional design; fashion; project methodology